Desi Divas : Political Activism in South Asian American Cultural Performances - Garlough, Christine, 1967- (Book collections on Project MUSE., 2013)
Desi Divas: Activism in South Asian American Cultural Performances is the product of five years of field research with progressive activists associated with the School for Indian Languages and Cultures (SILC), South Asian Americans Leading Together (SAALT), the feminist dance collective Post Natyam, and the grassroots feminist political organization South Asian Sisters. Christine L. Garlough explores how traditional cultural forms may be critically appropriated by marginalized groups and used as rhetorical tools to promote deliberation and debate, spur understanding and connection.